Empowerment of Future Frontline Indonesian Weather and Climate Information - Wiratmo, Joko; Siregar, Plato Martuani (Amirul Bangun Bangsa, 2025)
Climate change increases the frequency and intensity of hydrometeorological disasters in Indonesia. However, community climate literacy is still limited, thus hampering the speed of mitigation and adaptation efforts. For this reason, a program to empower prospective vanguards of weather and climate information is held as a strategic partner of BMKG in delivering information effectively and contextually. This program is in the form of interactive webinars, online discussions, and in the future can be in the form of field training, which will be collaborated with environmentally conscious family activities (Kadarling) to increase community capacity and climate literacy. This approach is expected to strengthen an inclusive early warning system and community resilience in dealing with climate change. The main outcome of this activity is primarily the increased knowledge about weather, seasons, and climate in Indonesia, along with the enhanced networking among researchers and observers of weather and climate from various backgrounds. This is evidenced by the relatively increased number of members in the WhatsApp group that was formed, which is still related to the webinar that was held.